Crossing taboo lines: ctizen journalism ethics in political crisis settings - Moyo, Last (Palgrave Macmillan, 2021)
The advent of the Internet and social media has arguably opened up and democratized journalism as a social and professional practice. Most recently, newer online and mobile phone practices, variously referred to as “citizen journalism”, “participatory journalism”, “citizen-generated media”, “unfiltered journalism”, “hyperlocal journalism”, “networked journalism” and “grass-roots journalism”, have entered the journalism landscape, albeit constituting themselves mainly as subaltern, deprofessionalized, deinstitutionalized and radical counterhegemonic spaces (Allan, 2013; Atton, 2002; Gillmor, 2006; Moyo, 2014). Over time, these practices have crystalized around the term “citizen journalism”, identified by the leading alternative and digital media scholars as: (a) journalism that is often associated with narratives of the ordinary people;